Effect of cement distribution type on clinical outcome after percutaneous vertebroplasty for osteoporotic vertebral compression fractures in the aging population - Zhou, Chengqiang; Liao, Yifeng; Huang, Shaolong; Li, Hua; Zhu, Ziqiang; Zheng, Li; Wang, Bin; Wang, Yunqing (Frontiers in Surgery, 2022)
Objective: The study aimed to investigate the effect of the type of bone cement distribution on clinical outcomes following percutaneous vertebroplasty (PVP) for osteoporotic vertebral compression fractures (OVCF) in the elderly. Methods: Retrospective analysis of 160 patients diagnosed with OVCF who underwent PVP treatment from March 2018 to December 2020. Based on the kind of postoperative bone cement distribution, bone cement was classified as types I, II, III, IV, and V. Visual Analog Scale (VAS), Oswestry Disability Index (ODI), Cobb angle, anterior vertebral height ratio, refracture rate of injured vertebrae, and incidence of adjacent vertebral fractures were compared for the five types before and after three days, and one year of operation. Results: VAS and ODI at three days and one year postoperative were significantly lower than those preoperative (P < 0.05) for all five distribution types. VAS and ODI for types I, II, and III were lower at one year postoperatively than for types IV and V (P < 0.05). There was no significant difference in Cobb angle and anterior vertebral body height ratio between preoperative and three days postoperative groups (P < 0.05); however, there were significant differences between three days and one-year postoperative and preoperative groups (P < 0.05). Following one year of surgery, the Cobb angle and the anterior vertebral height ratio of types IV and V were significantly different from those of types I, II, and III (P < 0.05), and there was a statistically significant difference between types IV and V (P < 0.05). In terms of the incidence of injured vertebral refractures and adjacent vertebral fractures, the evenly distributed types I, II, and III were significantly lower than the unevenly distributed types IV and V, and the incidence of type V was higher (P < 0.05). Conclusions: The clinical efficacy of cement distribution following PVP of types I, II, and III is better than that of types IV and V, which can better relieve pain with long-lasting efficacy and minimize the occurrence of refractures of injured vertebrae and adjacent vertebral body fractures.